Onychomycosis in patients with nail psoriasis: a point to point discussion. Issue 1 (15th August 2016) - Rigopoulos, Dimitrios; Papanagiotou, Vasilios; Daniel, Ralph; Piraccini, Bianca Maria
Summary: Onychomycosis is the most common nail disease and affects large parts of the population. Psoriasis is a frequently encountered skin disorder with nail involvement being found in up to 80% of the patients at some time of the course of the disease. It has been postulated that onychomycosis occurs more frequently in patients with nail psoriasis, but the results of studies in the literature are controversial. Moreover, onychomycosis could exacerbate psoriasis through Koebner phenomenon and the treatment of psoriasis could predispose to onychomycosis. Finally, the differential diagnosis could be a real challenge due to many same clinical signs, the high prevalence and the possible coexistence of the two diseases. This article attempts to enlighten all these different aspects of a very close relationship.